Mitochondrion-mediated iron accumulation promotes carcinogenesis and Warburg effect through reactive oxygen species in osteosarcoma - Shuo Ni (Cancer Cell International, 2020)
Abstract Background Iron metabolism disorder is closely associated with several malignant tumors, however the mechanisms underlying iron and the carcinogenesis in osteosarcoma are not yet well understood. Methods Cell proliferation ability of osteosarcoma cell lines was measured by CCK-8, EdU incorporation and colony formation assays. Cell cycle analysis was detected by flow cytometry. The carcinogenesis of osteosarcoma was measured by soft-agar formation, trans-well and Wound healing-scratch assay. Warburg effect was detected by Seahorse respirometry assays. Reactive oxygen species (ROS) level was measured by Dichlorodihydrofluorescein diacetate (DCFH-DA) fluorescent probes. Western blotting was used to measure the expression of mitoferrin 1 (SLC25A37) and mitoferrin 2 (SLC25A28). Iron level in vitro and vivo was detected by iron assay kit. RNAi stable cell lines was generated using shRNA. Results Iron promoted proliferation, carcinogenesis and Warburg effect of osteosarcoma cells. Iron-induced reactive oxygen species (ROS) played an important role in these processes. Iron accumulated more in mitochondrion than in cytoplasm, suggesting mitochondrion-mediated iron accumulation was involved in the development of osteosarcoma. Moreover, iron upregulated the expression of mitoferrin 1 (SLC25A37) and mitoferrin 2 (SLC25A28). Knock-down of mitoferrin 1 (SLC25A37) and mitoferrin 2 (SLC25A28) decreased the production of ROS. In addition, iron increased the expression of Warburg key enzymes HK2 and Glut1, and affected AMPK/mTORC1 signaling axis. Conclusions Mitochondrion-mediated iron accumulation promotes carcinogenesis and Warburg effect of osteosarcoma cells. Meanwhile, iron deprivation might be a novel effective strategy in the treatment of osteosarcoma.